2022
DOI: 10.1109/tii.2021.3130248
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion Detection Framework for the Internet of Things Using a Dense Random Neural Network

Abstract: The Internet of Things (IoT) devices, networks, and applications have become an integral part of modern societies. Despite their social, economic, and industrial benefits, these devices and networks are frequently targeted by cybercriminals. Hence, IoT applications and networks demand lightweight, fast, and flexible security solutions to overcome these challenges. In this regard, artificial-intelligence-based solutions with Big Data analytics can produce promising results in the field of cybersecurity. This ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…The results are better in comparison with the baseline approach. In [28], Latif et al proposed a dense random neural network (DnRaNN) technique to detect attacks in an IoT environment. The authors obtained an accuracy of 99.14% when using binary classification and 99.05% when using multiclass scenarios.…”
Section: Related Workmentioning
confidence: 99%
“…The results are better in comparison with the baseline approach. In [28], Latif et al proposed a dense random neural network (DnRaNN) technique to detect attacks in an IoT environment. The authors obtained an accuracy of 99.14% when using binary classification and 99.05% when using multiclass scenarios.…”
Section: Related Workmentioning
confidence: 99%
“…Refs. [21,22], authors found that the conventional Internet of Things (IoT) technology is used in the industrial sector. The extensive expansion of IoT in the industrial sector gives rise to the obstruction of information security.…”
Section: Related Workmentioning
confidence: 99%
“…A proficient and fast algorithm is needed to detect malicious attacks in IoV. DL algorithms provide more efficient performances than traditional ML algorithms [ 21 , 22 , 23 ]. For IDS, some commonly used DL algorithms are convolutional neural network (CNN), recurrent neural network (RNN), LSTM, and GRU.…”
Section: Introductionmentioning
confidence: 99%